Synthesis and Characterization of Submicron Hydroxyapatite from Calcium Nitrate Tetrahydrate: Implications of pH Variations in the Precipitation Process - Devi Diyah Ayu Prameswari; Chaterine Oktavia Anggaraeni; Luluk Edahwati; Sri Redjeki; Shinta Soraya Santi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Hydroxyapatite (HAp) is the primary mineral component of bone and tooth tissue. Submicron-sized HAp offers enhanced osteoconductive properties, enabling it to serve effectively as a scaffold to support osteoblast activity and new bone formation. In this study, HAp was synthesized from calcium nitrate tetrahydrate using the precipitation method. The main variable investigated was the pH, adjusted by the addition of ammonium hydroxide, which influenced the yield and Ca/P ratio of the resulting HAp. The synthesized HAp was characterized using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Atomic Absorption Spectroscopy (AAS Flame), UV-Vis spectrophotometry, and X-Ray Diffraction (XRD). The optimal HAp product was obtained at pH 11 and sintered at 800 °C, yielding a Ca content of 2.56% and a P content of 4.28%, resulting in a Ca/P ratio of 1.6719; consistent with the theoretical stoichiometric value of 1.67. This was supported by XRD analysis, which showed the highest intensity peak at 2θ = 31.74°, confirming the presence of hydroxyapatite. SEM analysis revealed a particle size of 460.8 nm and a porosity of 20.15%. These findings demonstrate that hydroxyapatite can be successfully synthesized via precipitation using calcium nitrate tetrahydrate under optimal conditions of pH > 11.